Baseline NAWM structural integrity and CBF predict periventricular WMH expansion over time. (12th June 2018) - Promjunyakul, Nutta-on; Dodge, Hiroko H.; Lahna, David; Boespflug, Erin L.; Kaye, Jeffrey A.; Rooney, William D.; Silbert, Lisa C.
Abstract : Objective: We aimed to describe and compare baseline cerebral blood flow (CBF) and microstructural characteristics of normal-appearing white matter (NAWM) within the vulnerable periventricular white matter hyperintensity (PVWMH) penumbra region in predicting white matter hyperintensity (WMH) growth over time. Methods: Fifty-two patients, aged 82.8 years, underwent serial brain MRI, including pulsed arterial spin labeling and diffusion tensor imaging (DTI). New WMH and persistent NAWM voxels in relation to WMH penumbra at follow-up were identified. Mean baseline CBF and DTI variables of the new WMH and persistent NAWM voxels were computed. Univariate analyses with paired t tests were performed. Generalized estimating equation analyses were used to compare the relationships of baseline CBF, and structural penumbras with WMH growth, controlling for confounders. Results: Low baseline CBF and fractional anisotropy, and high mean diffusivity (MD), were independently associated with new PVWMH voxels, with MD being the best predictor of WMH growth. A separate model demonstrated that radial diffusivity had the strongest relationship with WMH growth compared with CBF and axial diffusivity. Conclusion: CBF and DTI measures independently predict WMH growth over time. DTI is a more sensitive predictor of WMH growth than CBF, with WMH progression likely due to demyelinating injury secondary to low perfusion. Findings support the use of MD as a sensitive marker of NAWM vulnerability in future trials aimed at preserving WM integrity.